Space, Culture, and Escapism: Nightlife Venues at Bira Beach Bulukumba - Armi Indrayuni; Syamsu A. Kamaruddin; Arlin Adam; A Zulfikar Aliuddin (Sean Institute, 2024)
This research aims to examine the phenomenon of escapism at Bira Beach, South Sulawesi, with the aim of understanding the complex interactions between night entertainment workers, tourists and local communities in a tourism context. By adopting a constructivist and interpretative paradigm, this study uses qualitative methods including direct observation and in-depth interviews to collect data. This approach allows research to gain a comprehensive understanding of how the social and cultural reality at Bira Beach is constructed and handled through the practice of escapism. The research results show that escapism at Bira Beach acts as a mechanism of adaptation and resistance to social norms and economic pressures, while influencing social structure and local identity. This phenomenon is analyzed through the lens of relevant sociological theories: Pierre Bourdieu with the concept of